2021
DOI: 10.3389/fonc.2021.738534
|View full text |Cite
|
Sign up to set email alerts
|

Atractylenolide-I Sensitizes Triple-Negative Breast Cancer Cells to Paclitaxel by Blocking CTGF Expression and Fibroblast Activation

Abstract: This investigation was conducted to elucidate whether atractylenolide-I (ATL-1), which is the main component of Atractylodes macrocephala Koidz, can sensitize triple-negative breast cancer (TNBC) cells to paclitaxel and investigate the possible mechanism involved. We discovered that ATL-1 could inhibit tumor cell migration and increase the sensitivity of tumor cells to paclitaxel. ATL-1 downregulated the expression and secretion of CTGF in TNBC cells. Apart from inhibiting TNBC cell migration via CTGF, ATL-1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…This might also incline us to test higher doses (over 4 mg/kg) of ATL I in future studies. Accumulating evidence has indicated that ATL I has a promising effect on cancer treatment, at least including colon cancer, cervical cancer, and breast cancer [53][54][55][56][57]. Thus, this also inclines us to explore the effect of ATL 1 on treating the later stages of metabolic-associated fatty liver disease, such as liver fibrosis, and even liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This might also incline us to test higher doses (over 4 mg/kg) of ATL I in future studies. Accumulating evidence has indicated that ATL I has a promising effect on cancer treatment, at least including colon cancer, cervical cancer, and breast cancer [53][54][55][56][57]. Thus, this also inclines us to explore the effect of ATL 1 on treating the later stages of metabolic-associated fatty liver disease, such as liver fibrosis, and even liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Each nude mouse was subcutaneously injected in the right axilla with 2 × 10 6 MDA‐MB‐231 cells in the logarithmic growth phase. When the longest axis of the tumor was between 5 and 8 mm, the mice were randomly assigned to control, positive control (cisplatin, 5 mg/kg), low‐concentration AT‐1 treatment (25 mg/kg), and high‐concentration AT‐1 treatment groups (50 mg/kg) (Li et al, 2020; Qu et al, 2022; Wang et al, 2021), with six mice in each group. The drug was injected intraperitoneally every 2 days, and the tumor's longest axis (L) and longitudinal axis (R) were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…AT‐1 inhibits lung cancer cell growth and suppresses SP1 protein expression (Xiao et al, 2017). AT‐1 promoted the sensitivity of TNBC cells to paclitaxel by blocking connective tissue growth factor (CTGF) expression and fibroblast activation, further enhancing the chemotherapeutic effect of paclitaxel on tumors and reducing tumor metastasis to the lung and liver (Wang et al, 2021). AT‐1 also induced apoptosis in colorectal cancer (CRC) cells by disrupting JAK2/STAT3 signaling by inhibiting the glycolytic metabolic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In TME, CCN2/CTGF transformed various cells into CAFs (Hutchenreuther et al 2015, 2018; Leask 2020a). Moreover it is also reported that CCN2 is overexpressed in CAFs for various pathobiological functions (Hutchenreuther et al 2015, 2018; Liao et al 2019b; Wang et al 2021). These include tumor angiogenesis, tissue stiffness, cancer stemness, and induced chemotherapy resistance.…”
Section: Ccn‐family Proteins In Neoplastic Tissues and Microenvironme...mentioning
confidence: 99%